(x-2)*(x-4)=0

Simple and best practice solution for (x-2)*(x-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)*(x-4)=0 equation:


Simplifying
(x + -2)(x + -4) = 0

Reorder the terms:
(-2 + x)(x + -4) = 0

Reorder the terms:
(-2 + x)(-4 + x) = 0

Multiply (-2 + x) * (-4 + x)
(-2(-4 + x) + x(-4 + x)) = 0
((-4 * -2 + x * -2) + x(-4 + x)) = 0
((8 + -2x) + x(-4 + x)) = 0
(8 + -2x + (-4 * x + x * x)) = 0
(8 + -2x + (-4x + x2)) = 0

Combine like terms: -2x + -4x = -6x
(8 + -6x + x2) = 0

Solving
8 + -6x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(2 + -1x)(4 + -1x) = 0

Subproblem 1

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {2, 4}

See similar equations:

| x-24-29-296=360 | | (X-24)-29-296=360 | | (x+2)*(x-4)=0 | | 13-22x=2+24x | | 9+6Y=3 | | (x-2)*(x+4)=0 | | -(7x-12)=2(x-1)+104 | | x+(x*.0825)=y | | .026x+5.103=.01x+5.095 | | .25(y-4)+.08y=.23y-.05(40) | | 3/4(4k-1)4/3(3k-2) | | (3x+18)-93=180 | | .5x+.38(200)=.25(236) | | 3x+18-93=180 | | .3(x+10)+.7x=18 | | x+5=8+2x | | x+5=4+x | | 2/3(x^2-1)^3/2 | | .3(x+10)+.07x=18 | | h=1+25t-5t^2 | | 0.5m= | | .36(12)+.06x=.18(30+x) | | .12(6)+.02x=.04(12+x) | | 320+80x=7208-220 | | m=4p-11 | | P(x)=-24x+336x-136 | | .15x+.05(2-x)=.7(-1) | | 36x^2+49-84=0 | | 5(2x-1)=(x+4) | | 3x+8=3y | | 1.00*55=1.66*x | | .5x-3.1=.4 |

Equations solver categories